2016
DOI: 10.5964/ejop.v12i1.1043
|View full text |Cite
|
Sign up to set email alerts
|

Are there similar or divergent transitions to adulthood in a Mediterranean context? A cross-national comparison of Italy and Spain

Abstract: The purpose of this study was to examine the differences and similarities between Italy and Spain in regard to emerging adults’ perceptions of identity status, autonomy, attachment, and life satisfaction. The goal was to verify whether a Mediterranean model of transitions from adolescence to adulthood exists. Three hundred and forty undergraduate students (171 Italians and 169 Spanish) ranging in age from 19 to 22 completed measures of identity status, emotional autonomy, attachment style, and life satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…Moreover, within the final stages of the HMR, no significant effect was found for the interaction between OXTR rs53576 and the parental bonding dimension on anxiety or avoidance, not confirming the first hypothesis. Overall, these results suggest that the quality of familiar bonds in this population, where higher levels of expressed emotions often characterize the relationship between parents and offspring [ 19 , 67 , 68 ], could affect the experience of close relationships in adulthood more independently of the genetic sensitivity, invalidating the starting HP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, within the final stages of the HMR, no significant effect was found for the interaction between OXTR rs53576 and the parental bonding dimension on anxiety or avoidance, not confirming the first hypothesis. Overall, these results suggest that the quality of familiar bonds in this population, where higher levels of expressed emotions often characterize the relationship between parents and offspring [ 19 , 67 , 68 ], could affect the experience of close relationships in adulthood more independently of the genetic sensitivity, invalidating the starting HP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, within the final stages of the HMR, no significant effect was found for the interaction between OXTr rs53576 and parental bonding dimension on anxiety or avoidance, not confirming the first hypothesis. Overall, these results suggest that the quality of familiar bonds in this population, where higher levels of expressed emotions often characterize the relationship between parents and offspring [19,64,65], could affect the experience of close relationships in adulthood more independently from the genetic sensitivity, invalidating the starting HP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Although during emerging adulthood the dependence on the family of origin decreases while the dependence on other figures, such as peers and romantic partners, becomes more important (Laible, Carlo, & Raffaelli, 2000), our data show that both parental attachment bonds and positive quality of sibling relationships are predictive of the psychological outcome of emerging adults. The good quality of family relationships and a higher well-being can favor the transition toward adulthood, supporting the emerging adults in their development tasks linked to the achievement of residential, economic, and work aspects (Pace et al, 2016). This is especially in Italy, where emerging adults tend to live with their parents longer than in other European countries (Sestito & Sica, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially in Italy, where emerging adults tend to live with their parents longer than in other European countries (Sestito & Sica, 2014). In fact, previous research on Italian emerging adults has shown that an insecure attachment characterized by low emotional autonomy from parents and poor emancipation from patterns of parent–child relationships results in a less advanced (adult) identity status (foreclosure, moratorium) and less life satisfaction (Pace et al, 2016). According to Scabini (2000):The slowdown of the transition to adulthood highlights the importance of the family of origin: in fact, this last one represents the warm nest in which to recover one’s strengths and to assemble a better equipment in order to face the uncertain and complex adult world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation